The Umbrella Act as a Solution to Conflicting Laws and Regulations During the Covid-19 Pandemic - E A, M. Kenza Radhya; Nurifanti, Ersya Dwi (Yuridika, 2021)
The Covid-19 pandemic has brought significant new challenges to countries around the world. In Indonesia, the detrimental effects of the pandemic have been exacerbated by contradictory government policies, which have hindered the nation's ability to control the situation. The proposed Umbrella Act, covering both health and the economy, could resolve the conflict inherent in government policies, and therefore help Indonesia provide an integrated response to the pandemic. This in turn could bring down the country's Covid-19 case numbers, which remain relatively high. This study uses a normative method to critically analyse the legal and regulatory issues of the Umbrella Act. By introducing it, the Indonesian government will be able to fulfil its responsibilities to the national community and effectively mitigate the current emergency.